Registration of 'Griffin' Winter Canola. Issue 2 (6th February 2015) - Stamm, Michael; Cramer, Gary; Dooley, Scott J.; Holman, Johnathon D.; Phillips, Dan; Rife, Charlie L.; Santra, Dipak K.
Abstract : 'Griffin' (Reg. No. CV‐25, PI 672148), is a canola‐quality, winter oilseed rape ( Brassica napus L.) and is a dual‐purpose forage and grain canola cultivar developed for Kansas, with potential to be grown across the southern Great Plains. It was tested as the experimental cultivar KS4022 and was released by K‐State Research and Extension. The ability of Griffin to withstand the effects of simulated grazing and its excellent forage quality compared with 'Wichita' make it a good candidate for dual‐purpose use. In simulated grazing studies, Griffin had winter survival superior to Wichita across all treatments; Griffin averaged 80.4% survival across grazing treatments, whereas Wichita averaged 69.4%. At the optimum timing for forage harvest, Griffin's final grain yield was reduced by 36.6%, while Wichita's final grain yield was reduced by 61.1% compared with the no‐forage harvest treatment. Griffin yields a high‐protein, highly digestible, nutritious forage for livestock producers. Griffin also possesses beneficial morphological features that could be used in breeding of new cultivars. A prostrate growth habit and the ability to avoid fall stem elongation are important characteristics to consider when selecting a canola cultivar with optimum winter survival.